COMPARISON OF PUBLIC TRANSPORT SERVICES ORGANIZATION IN THE PRAGUE AND WARSAW METROPOLITAN REGIONS - Damian GĄSKA; Martin TRPIŠOVSKÝ; Maria CIEŚLA (Scientific Journal of Silesian University of Technology. Series Transport)
This paper presents a selective comparison of the organization of public transport in the metropolitan regions of Prague and Warsaw. A brief description of the regions and the specification of the most important characteristics of public transport systems has been shown.